CD4+ T-Cell-Independent Secondary Immune Responses to Pneumocystis Pneumonia - de la Rua, Nicholas M.; Samuelson, Derrick R.; Charles, Tysheena P.; Welsh, David A.; Shellito, Judd E. (Frontiers in Immunology, 2016)
Pneumocystis pneumonia is a major cause of morbidity and mortality among immunocompromised patients, especially in the context of HIV/AIDS. In the murine model of Pneumocystis pneumonia, CD4+ T-cells are required for clearance of a primary infection of Pneumocystis, but not the memory recall response. We hypothesized that the memory recall response in the absence of CD4+ T-cells is mediated by a robust memory humoral response, CD8+ T-cells, and IgG-mediated phagocytosis by alveolar macrophages. To investigate the role of CD8+ T-cells and alveolar macrophages in the immune memory response to Pneumocystis, mice previously challenged with Pneumocystis were depleted of CD8+ T-cells or alveolar macrophages prior to re-infection. Mice depleted of CD4+ T-cells prior to secondary challenge cleared Pneumocystis infection within 48 h identical to immunocompetent mice during a secondary memory recall response. However, loss of CD8+ T-cells or macrophages prior to the memory recall response significantly impaired Pneumocystis clearance. Specifically, mice depleted of CD8+ T-cells or alveolar macrophages had significantly higher fungal burden in the lungs. Furthermore, loss of alveolar macrophages significantly skewed the lung CD8+ T-cell response toward a terminally differentiated effector memory population and increased the percentage of IFN-γ+ CD8+ T-cells. Finally, Pneumocystis-infected animals produced significantly more bone marrow plasma cells and Pneumocystis-specific IgG significantly increased macrophage-mediated killing of Pneumocystis in vitro. These data suggest that secondary immune memory responses to Pneumocystis are mediated, in part, by CD8+ T-cells, alveolar macrophages, and the production of Pneumocystis-specific IgG.